The efficacy of intracisternal irrigation of papaverine on cerebral blood flow in patients with subarachnoid hemorrhage - Shanmugaiah, Anand; Kumar, R Raj; Babu, VT Suresh (Nepal Journal of Neuroscience, 2023)
Background: Cerebral vasospasm remains the most common cause of death in patients after subarachnoid hemorrhage despite various treatments. This study was conducted to find the efficacy of intracisternal washing with papaverine on cerebral blood flow. Materials and Methods: This study was performed on 40 patients and totally 120 arteries in 2022. Cerebral blood flow velocity changes before and after washing with papaverine were measured and analyzed. Results: Twenty (20) patients with anterior communicating artery (ACOM) aneurysm and 20 patients with middle cerebral artery (MCA) aneurysm were assessed. Mean blood flow velocity before aneurysm and before washing in ACOM and MCA was 66.2±13.8cm/s and 62.86±7.3cm/s, respectively, which reached 20.45±4.17 cm/s and 32.1±7.7 cm/s, respectively after washing (P value = 0.016 and 0.024). Mean blood flow after aneurysm and before washing in ACOM and MCA was 93.2±10.9 cm/s and 69.44±12.2 cm/s, respectively, which reached 33.29±4.2cm/s and 40.01±5.28 cm/s, respectively after washing (P value = 0.001 and 0.01). Conclusion: Intracisternal irrigation with papaverine significantly reduces cerebral blood flow and relieves vasospasm.